THE INCREDIBLE : DARK SON - Pak, Greg (New York, NY: MARVEL WORLDWIDE, INC., 2011)
As the dark son rises, the universe will fall! All his life, the Hulk has wanted to be left alone; now, he's got a big, bad family to keep up with. They'd better stick together no matter how uncomfortable this new arrangement may be for all concerned, because one more addition to the family is making his way across the galaxy: the world-shattering Hiro-Kala.
Chapters 5-8/ Writer: Greg Pak ; Pencils/Breakdowns: Barry Kitson ; Inks/Finishes: Barry Kitson & Scott Hanna with Jay Leistein ; Colors: Matt Milla ; Letters: Simon Bowland
"Contains material originally published in magazine form as Incredible Hulks #612-617."
Keywords: Incredible Hulk (Fictitious character) -- Comic books, strips, etc; Hulk (Fictitious character) -- Comic books, strips, etc; Comic books, strips, etc; Graphic novels